Clinical Profile of Mucormycosis during the Second Wave of COVID-19 in a Tertiary Care Center in India - Kunhiparambath, Sunil Kumar; Oommen, Beena; Keeriyatt Govindan, Sajeeth Kumar; Nair, Karichery Shilpa; Madayambath, Sagesh (International Journal of Integrated Health Sciences, 2023)
Objective: To study the clinical profile and treatment outcome of mucormycosis associated with the second wave of COVID-19 pandemic.Methods: An observational study was conducted in a tertiary care center over a period of 12 months, including a 6-month post treatment follow up. Study included all COVID positive patients with a clinical and radiological evidence of rhino-orbito-cerebral mucormycosis during the second wave of COVID-19. All patients underwent further diagnostic workup and confirmed cases underwent surgical debridement and Amphotericin B was started.Results: A total of 59 patients presented with mucormycosis with the mean age being 52.7 years and unilateral facial and orbital edema as the most common symptoms (28.8%). All were diabetic with HbA1c >7 in 54.2%. The mean duration of presentation was 20.7±7.9 days from the onset of COVID-19 infection. Unilateral involvement of the paranasal sinuses was the most common finding in MRI. Early administration of Amphotericin B with prompt surgical debridement was performed in all cases. Orbital exenteration was conducted in nine patients for better fungal load clearance. Patients showed a good response to surgical debridement and prompt medical treatment, with a mortality rate of 27%.Conclusion: COVID-19 associated mucormycosis is difficult to treat and often presents in late stage. Uncontrolled diabetes, immunocompromised state, and steroid-induced immunosuppression were important risk factors. A close surveillance for early identification and initiation of treatment is mandatory. Repeated surgical debridement to clear the dead tissue is effective to control fungal load.